PENGARUH BIRTH BALL TERHADAP PENURUNAN NYERI PADA IBU BERSALIN KALA I FASE AKTIF DI BPM SUNARTI TAHUN 2022 - Nurrahmaton Nurrahmaton; Nuiah Arma; Melati Melati (Jurnal Kesehatan dan Fisioterapi, 2022)
Abstract - Pain is experienced by many women during childbirth. Various attempts have been made to reduce pain both pharmacological and non-pharmacologically. One of the non-pharmacological methods is physical therapy using a ball or often called a Birth Ball. The benefit is to provide experience for both health workers and maternity mothers so that they can apply the Birth Ball method as a way to reduce pain so as to improve the quality of normal delivery. The study aimed to determine the effect of Birth Ball on reducing pain before and before being given treatment to mothers at BPM Sunarti in 2022.This study was a pre-experiment with one group pretest posttest design. It was conducted in August 2022. The research sample was 10 primigravidainpartu maternal using purposive sampling. The pain scale was measured using the Bourbanis scale, the results of which were recorded directly on the observation sheet. The statistical test used was Wilcoxon with value = <.05.The results showed the value of Sig = .005 which means α = <.05, it was found that there was an effect of Birth Ball on Reducing Pain Scale in Maternity Mothers during the Active Phase 1 at BPM Sunarti in 2020.The conclusion showed an effect of the Birth Ball on reducing pain in active mothers found in BPM Sunarti 2020. It is recommended to midwives who work at BPM Sunarti to consider the Birth Ball method as a way to reduce labor pain in normal delivery mothers. Keywords: Birth Ball, Pain Reduction, Scale